Measuring Residents’ and Visitors’ Satisfaction with Sustainable Tourism—The Case of “Rusanda” Nature Park, Vojvodina Province - Trišić, Igor; Privitera, Donatella; Ristić, Vladica; Štetić, Snežana; Stanić Jovanović, Sara; Nechita, Florin (MDPI AG, 2023)
The Nature Park “Rusanda” (NPR) is a designated area under the second category of national protection. Situated in the Vojvodina Province, in the northern region of Serbia, its accessibility to a substantial number of international visitors is enhanced by its proximity to Romania and Hungary. Lake Rusanda and the salt marsh habitats render this region a sanctuary for rare avian species. This ecological significance has led to the NPR being designated as an IBA area—an Important Bird and Biodiversity Area by Birdlife. Beyond its natural attributes, the NPR stands out for its diverse cultural heritage, stemming from the local population residing in its immediate vicinity. A notable characteristic is the diverse ethnic makeup, contributing to a wide array of cultures, traditional attire, original folk music, customs, and cuisine, collectively forming a distinctive cultural heritage unique to this part of Vojvodina. To assess the status of sustainable tourism and its impact on the satisfaction of both residents and tourists within the NPR, the Prism of Sustainability model (PoS) is employed. In the quantitative approach, a survey questionnaire was utilized as a research tool, with a total of 840 participants included through a randomized sampling technique. Regression analysis of the study’s results indicates that sustainable tourism exerts a significant influence on the contentment of local people and tourists in the NPR. Given the presence of diverse ecological and societal elements, in addition to the existence of rare flora and fauna species, the central thrust in tourism development should focus on preserving and involving local residents in the planning and progress of tourism initiatives. The primary types of tourism that are poised for success in the NPR encompass ecotourism, wellness and spa tourism, nature-based tourism, birdwatching, scientific research tourism, and excursions.
Keywords: sustainable tourism; prism of sustainability; local community